Perancangan Interior Fasilitas Okupasi Bagi Para Skizofrenia (Gangguan Jiwa) di Surabaya - Sitanto, Olivia; wardani, laksmi kusuma; Suryanata, Linggajaya (Intra, 2016)
Schizophrenia is one of the phenomena that deviate from a person who lost a sense of reality that happened at productive age with different causes. Every year the numbers of patients always increase and place for the patients continues to decrease. There is a solution for the patients, maximizing the therapy process by creating an atmosphere around the environment, which patients needed. Responding to that solution, Interior function can be the one kind of therapy, which indirectly affects the healing process. It is also a concern for schizophrenia people who deserve to be given the same facilities like other people. This design based on interior psychology approach and the effect against psychology of the patients. Healing garden is one of the designs that is used for healing. The facilities which given are works therapy facilities like batik, sewing, painting, music, sports, counseling, and gallery.